Quasi-stationary streamer propagation - Bolotov, O.; Kadolin, B.; Mankovskyi, S.; Ostroushko, V.; Pashchenko, I.; Taran, G.; Zavada, L. (Вопросы атомной науки и техники, 2015)
The numerical simulations are carried out for the quasi-stationary stage of the axially symmetric streamer propagation and for the linear stage of its azimuthal perturbation development. The dependences of the streamer velocity on the average electric field strength are obtained for the different assumptions about photo-ionization intensity. Azimuthal instability is revealed and its connection with the streamer branching is discussed.